2014
DOI: 10.1038/nprot.2014.022
|View full text |Cite
|
Sign up to set email alerts
|

Universal sample preparation method integrating trichloroacetic acid/acetone precipitation with phenol extraction for crop proteomic analysis

Abstract: Crop plants contain large amounts of secondary compounds that interfere with protein extraction and gel-based proteomic analysis. Thus, a protein extraction protocol that can be easily applied to various crop materials with minimal optimization is essential. Here we describe a universal protocol for total protein extraction involving trichloroacetic acid (TCA)/acetone precipitation followed by SDS and phenol extraction. Through SDS extraction, the proteins precipitated by the TCA/acetone treatment can be fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 61 publications
1
131
0
Order By: Relevance
“…Samples were prepared with protocols adapted from Wang et al (2006) and Wu et al (2014). Frozen aerial tissues were macerated in liquid nitrogen with a mortar and pestle.…”
Section: Cell Lysis and Protein Extraction For Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were prepared with protocols adapted from Wang et al (2006) and Wu et al (2014). Frozen aerial tissues were macerated in liquid nitrogen with a mortar and pestle.…”
Section: Cell Lysis and Protein Extraction For Enrichmentmentioning
confidence: 99%
“…Specifically, we pulsed Aha into Arabidopsis seedlings and allowed nascent proteins to be labeled for 3 h at room temperature. To remove nonprotein contaminants and obtain better quality samples for mass spectrometry, we isolated total protein from seedlings via trichloroacetic acid-acetone precipitation followed by phenol extraction (Wang et al, 2006;Wu et al, 2014).…”
Section: Boncat Can Be Used To Enrich Newly Synthesized Proteins In Amentioning
confidence: 99%
“…In addition, ZEB1 was identified as an independent prognostic factor of GC, and there is a significant correlation between ZEB1 expression and diffuse phenotype in GC [38]. Previous studies suggested that a variety of factors such as microRNAs (miRNAs) and ubiquitin ligase CUL4A can regulate the EMT process by modulating ZEB1 expression [40][41][42][43][44]. Our study provided new evidence that Neo1 promoted the EMT process in GC by regulating the expression of ZEB1.…”
Section: Discussionmentioning
confidence: 49%
“…The aqueous phase dissolves cell debris, nucleic acids, and carbohydrates, while the phenolic phase carries proteins and lipids [29]. Proteins from the phenolic phase are then precipitated with methanol and ammonium acetate [30].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, three spots were found at low molecular levels, with an approximate molecular mass in the range of 10 and 20 kDa. In fact, according to several studies of cardoon's protein profile [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], proteins with low Mw, represented the ÎČ-subunits of cardosins (16.5 and 13.5 kDa), since there were a positive correlation between band intensities and milk-clotting activities.…”
Section: Protein Separation On 2d-e and Maldi-tof-ms Identificationmentioning
confidence: 99%